Principles of revitalisation of derelict rural buildings - Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2003)
The problem of Lithuanian derelict and mismanaged rural buildings that have a negative influence on the economy and environment of the country is analysed in the paper. Revitalisation of unused rural buildings is analysed in a context of sustainable development. Factors determining distribution and revitalisation perspectives of unused buildings were established by using methods of mathematical statistics. It was estimated that the peculiarities of territorial distribution are different in various zones of different development activity, also they differ according to the uses of buildings. Analytical review of sustainability indicator systems was performed. The model of indicator system for revitalisation of derelict rural buildings is proposed in the paper. This indicator system was worked out according to the common principles of sustainable development and to local peculiarities, explored by analysing territorial distribution of objects. It is possible to rate the priorities of building revitalisation alternatives by using the proposed model of the system with the help of multiple criteria decision-making methods. Due to incomplete and inconsistent information regarding sustainable development, the author suggests to use fuzzy set theory.First Published Online: 26 Jul 2012